Prinsip Pengawasan Independensi Hakim - Kusnu Goesnadhie S. (Jurnal Hukum IUS QUIA IUSTUM, 2007)
Judicial independence is best understood as a two dimensional relationship. Firstly, in terms of the sources of dependency, external controls and influences must be distinguished from internal controls and influences. Secondly, in terms of the targets of influence or control, the individual judges must be distinguished from the judiciary as a collective whole or institution. Judicial independence is a pre-requisite to the rule of law and a fundamental guarantee of a fair trial.